2022
DOI: 10.3758/s13423-022-02089-x
|View full text |Cite
|
Sign up to set email alerts
|

A vigilance decrement comes along with an executive control decrement: Testing the resource-control theory

Abstract: A decrease in vigilance over time is often observed when performing prolonged tasks, a phenomenon known as “vigilance decrement.” The present study aimed at testing some of the critical predictions of the resource-control theory about the vigilance decrement. Specifically, the theory predicts that the vigilance decrement is mainly due to a drop in executive control, which fails to keep attentional resources on the external task, thus devoting a larger number of resources to mind-wandering across time-on-task. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…From a theoretical standpoint, the ndings from the current experiment do not align with the resource control model 20 . Note that recent work that has assessed the resource control theory has focused on how executive control declined over the course of the task and neglected the MW aspect 22 . Here, our manipulations have resulted in evidence that MW is an unreliable predictor of vigilance decrement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical standpoint, the ndings from the current experiment do not align with the resource control model 20 . Note that recent work that has assessed the resource control theory has focused on how executive control declined over the course of the task and neglected the MW aspect 22 . Here, our manipulations have resulted in evidence that MW is an unreliable predictor of vigilance decrement.…”
Section: Discussionmentioning
confidence: 99%
“…As we can surmise, this model proposes that MW and vigilance decrement are two highly dependent processes. However, to date, empirical evidence on this theoretical model is still scarce 22 . In this vein, studies have shown that MW increases as a function of time-on-task 6,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Before commencing the experiment, they signed a consent protocol approved by the Ethics Committee of Southwest University. The result of the post-hoc power analysis showed 1 0.99 for the observed main effect of the cue with FD as dependent variable [ 0.83 0.05 28 , run with G*Power 3 ( Luna et al, 2022b )].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, various interactions between alertness and executive function have been found. Executive function has been proved to be associated with vigilance decrement ( Luna et al, 2018 , 2022b ), and phasic alertness can enhance the global and automatic processing of visual stimuli and further inhibit executive control performance ( Weinbach and Henik, 2011 ; Weinbach et al, 2015 ; Tanzer et al, 2016 ; Zani and Proverbio, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that this greater vigilance among diet-sensitive individuals makes them more susceptible to numerosity effects for relevant nutrient contents (e.g., sugar content for individuals with diabetes), compared to the general population. This prediction derives from the fact that vigilance, or even simply paying attention, requires cognitive resources that are limited in supply (Luna et al, 2022). For example, the more that one is vigilant about some stimulus, it has been shown that this actually decreases the amount of cognitive resources that this person can expend on subsequent tasks, including decision-making and choice tasks.…”
Section: Nutrition Labeling and Vigilance For Nutrient Contentsmentioning
confidence: 99%